Vibroacoustic Study of a Miniature Jet Engine Under Blade-Casing Rubbing Condition - Bartłomiej Cywka; Wojciech Prokopowicz; Bartosz Ciupek; Grzegorz M. Szymański; Daniel Mokrzan; Andrzej Frąckowiak (Energies)
Turbine engines are currently one of the most important and expensive aircraft components. Both for economic and safety reasons, high engine reliability is required. Therefore, sophisticated methods are needed to determine their current condition. Diagnostics of turbine engines allow for the detection of faults before they lead to damage. The article presents methods and results of vibroacoustic diagnostics of a miniature GTM400 jet engine adapted to kerosene and hydrogen fuel supply. During thermal and vibroacoustic tests of engine parameters powered by hydrogen fuel supply, the engine seized up in the initial start-up phase due to improper control and rapid thermal changes in the gas line. The cause of the undesirable technical condition of the engine was a significantly higher temperature of gases (exhaust gases) affecting the working elements of the engine (turbine shaft, rotor, and blades), which consequently led to engine damage. This phenomenon and the results obtained from the unexpected technical condition constitute a valuable premise for considering the issue of proper operation of the turbojet engine during fuel changes, especially following current trends related to the decarbonization of the aviation sector. The obtained research results and the resulting observations and conclusions make it necessary to perform technical analyses and pre-implementation tests each time before allowing the use of a conventional engine if it undergoes the process of reconstruction in terms of using a new fuel (especially if its technical parameters are different from the originally used one). The presented method of conducting tests allows for a detailed determination of the causes of damage to the cooperating elements of the engine structure under the influence of changes in operating parameters.